EDUKASI TENTANG TANDA BAHAYA NYERI KEPALA PADA PELAJAR DI KOTA MATARAM - Hunaifi, Ilsa; Primayanti , Ika; Dwi Febrian, Haldy; Ammar Rusydi, Muhammad; Puspasari Mahadewi, Ni Made; Mutiara Syifa, R.R. Ditya; Wahyu Maharani, Amelia; Sapta Wardhani, Indah (Universitas Mataram, 2024)
Headache is a common symptom in both children and adolescents which impacts quality of life, health, and social functioning. Most headaches are primary headaches, but the presence of red flags may indicate the possibility of secondary headaches. The purpose of this education program is to increase awareness and insight among students in Mataram City regarding the red flags of headache thus they could be more aware if having one of the signs. The Education was attanded by 96 students at SMAN 1 and SMAN 3 Mataram using counseling method by presenting content using power point and followed by presenting illustrative video and flyer about signs and red flags of headache for students. Pre- and post-test were done using google form to evaluate participants' knowledge and understanding. The pre- and post-test questions consisted of 5 multiple choice questions, with an average score on the pre-test was 41.5 and the average score on the post-test was 70.6. These results show an increase in knowledge and understanding related to the red flags of headaches in students. Education is a solution to increase knowledge for detecting red flags of headache among students.